Environmental Law from a Human Rights Perspective and Effective Government Management - Caminada Vallejo, Romina (2015)
This article takes us through the development of environmental law and the victories he has achieved in a long journey to start being part of national political agendas of countries and a global concern. Also leads us to analyze the different recognition elements necessary for success in environmental protection, in terms of environmental law implementation is efficient and effective. Thus reading the article leads us down the path of recognizing situations and elements necessary for the triumph of environmental law. The first, the consideration that this branch of law gets treatment as a human right which allows the category and gives the treatment it deserves. The second key element recognized as environmental law is the absolute principle of sustainability as rector of environmental policies, which should be based on an economic analysis, political, social, cultural and ecological decisions based on ethics. At the same time, the analysis is performed by Otis Duncan developed over th